Sistem Informasi Akuntansi Pendapatan Penjualan Pada Usaha Dagang Bahan Bangunan - Dede Saefudin; Muhammad Faittullah Akbar; Rizal Amegia Saputra; Eka Fitriani (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
In managing business revenue, the sale of raw materials for the owner uses manual methods that are often constrained in managing financial statements and recording revenue accounting so that in the financial reporting period there are often delays so that a computerized system is needed to handle these problems. In this case, the author focuses on the problem of recording data on sales of goods and income transactions starting from recording the purchase of goods, data collection of goods, storage. Data related to the sales process to the process of making reports. With the description of the problem, the author implements a desktop-based application as a tool for managing financial data for trading businesses and provides time and human resource efficiency. The method used is Waterfall and system design using the UML (Unified Modelling Language) method. The result achieved is a sales revenue accounting information system that can support the processing of revenue data with a computerized system using desktop-based Java Netbeans, so that effective and efficient activities can be achieved in supporting business activities in revenue management. The measurement with the blackbox testing test by producing a valid average in each application procedure that is carried out.